The identity of Jerieng community in negotiating culture - Herdiyanti Herdiyanti; Panggio Restu Wilujeng; Putra Pratama Saputra (Masyarakat, Kebudayaan dan Politik, 2020)
Malay identity is the most dominant cultural identity in Bangka Belitung that still holds their strength of local wisdom even though modernization, afforded by tin mining and palm oil exploration, is emerging around them.  One of the original Malay people in Bangka Belitung is the Jerieng community. This study is aimed to identify negotiations on the boundaries of the cultural identity of the Jerieng community in West Bangka Regency. This study used the theory of identity building from Manuel Castells and subculture theory. This study also employs a descriptive qualitative approach intended to describe the common symptoms associated with the distribution of Malay culture in the Bangka Belitung Islands Province, especially the Jerieng community. In this study, ten informants were interviewed, consisting of the six elders and four from the younger generation. The locations of this research were Ibul Village, Pelangas Village, and Kundi Village, West Bangka Regency, which was the Jerieng community area. The study results showed that the Jerieng community had a way of maintaining the cultural identity by maintaining the values and norms of their ancestral heritage and harmony between people, the environment, and the natural environment. Meeting with culture outside made the Jerieng community negotiate their identity to form the construction of surviving, changing, identity, and negotiating cultural identity. The Jerieng community’s identity was still maintained, including a pilgrimage to sacred tombs, mountain alms, circumcision, and language dialects, while the Jerieng community identity has changed, including village charity, traditional clothing, prayer during the Prophet’s birthday, and rituals of spells. Furthermore, the identity of the Jerieng community, including custom clothing and jewelry, language dialects, and the marriage system, is applied through the negotiation process by continuing to carry out some traditions or cultures considered still relevant to people’s lives at this time.